Moravian sermon, harvest festival (1962)
This item is a Moravian sermon originally written for the Harvest Festival, October 14, 1962. It was reused several times for service in Makkovik including on September 27, 1964 and October, 1968. The author is unknown. Title based on the contents of the record.